Numerical simulation of effective heat recapture ammonia pyrolysis system for hydrogen energy - Lim, Jian Tiong (2024)
This paper proposes a solution to address the challenges of high storage and transport costs associated with using hydrogen ((Formula presented.)) as an energy source. It suggests utilizing ammonia ((Formula presented.)) as a hydrogen carrier to produce (Formula presented.) onsite for hydrogen gas turbines. (Formula presented.) offers higher volumetric hydrogen density compared to liquid (Formula presented.), potentially reducing shipping costs by 40%. The process involves (Formula presented.) pyrolysis, which utilizes the heat waste from exhaust gas generated by gas turbines to produce (Formula presented.) and nitrogen ((Formula presented.)). Numerical simulations were conducted to design and understand the behaviour of the heat recapture (Formula presented.) decomposition system. The design considerations included the concept of the number of transfer units and heat exchanger efficiency, achieving a heat recapture system efficiency of up to 91%. The simulation of (Formula presented.) decomposition was performed using ANSYS, a commercial simulation software, considering wall surface reactions, turbulent flow, and chemical reaction. Parameters such as activation energy and pre-exponential factor were provided by a study utilizing a nickel wire for (Formula presented.) decomposition experiments. The conversion of (Formula presented.) reached up to 94% via a nickel-based catalyst within a temperature range of 823 K to 923 K which is the exhaust gas temperature range. Various factors were considered to compare the efficiency of the system, including the mass flow of (Formula presented.), operating gauge pressure, mass flow of exhaust gas, among others. Result showed that pressure would not affect the conversion of (Formula presented.) at temperatures above 800 K, thus a lower amount of energy is required for a compression purpose in this approach. The conversion is maintained at 94% to 97% when lower activation energy is applied via a ruthenium-based catalyst. Overall, this study showed the feasibility of utilizing convective heat transfer from exhaust gas in hydrogen production by (Formula presented.) pyrolysis, and this will further enhance the development of (Formula presented.) as the potential (Formula presented.) carrier for onsite production in hydrogen power generation.